Does clinically measured ankle plantar flexor muscle strength or weakness correlate with walking performance in healthy individuals? - Akalan, N.Ekin; Kuchimov, Shavkat Nadir; Temelli, Yener; Ören, Merve; Nene, Anand; APTİ, ADNAN (My University, 2018)
OBJECTIVE: Muscle strength is usually measured using isometric hand-held dynamometers (HHDs) in the clinic. However, during functional activities, the muscle acts more dynamically. The aim of this study was to investigate the relation between clinically measured plantar flexor (PF) muscle strength (PFMS) and laboratory measurements of peak ankle plantar flexion power generation (APFPG), peak ankle moment (PAM), peak plantar flexion velocity (PFV) and mean gait velocity in healthy participants. METHODS: The maximum PFMS on non-dominant sides in 18 able-bodied persons 23.88 (SD 3.55 years) was measured before (Pre-S) and after a stretching (Post-S) procedure (135 sec. x 13 rep. with 5 sec. rest) by using a HHD. The stretching procedure was used to generate temporary PF muscle weakness. Gait analysis was carried out for Pre-S and Post-S conditions. Normalized (by weight and height) and non-normalized HHD scores and differences for both conditions were correlated by Pearson correlation coefficient calculations (p < 0.05). RESULTS: Reduced PFMS (%23, p < 0.001) in Post-S, according to the HHD scores, has only a weak correlation with APFPG (r > 0.3, p < 0.5). Gait velocity was found to be strongly correlated with APFPG only in the Post-S condition (r = 0.68, p < 0.002). HHD scores and PAM were moderately correlated with the non-normalized Post-S condition (r = 0.44, p = 0.70) and strongly correlated with the non-normalized Pre-S condition (r = 0.62, p < 0.01). DISCUSSION: HHD scores of plantar flexor muscles give very limited information about the PF performance during walking in healthy individuals. Simple normalization did not improve the relations. Clinically measured isometric muscle strength and muscle weakness have only moderate strengths for establishing a treatment protocol and for predicting performance during walking in neurologically intact individuals.
Keywords: Gait; Muscle Strength; Performance; Relationship; Stretching; Plantar Flexor